Sustainable practices management: Case in paddy farming in West Malaysia - Othman, Zakirah; Musa, Suria; Che Ali, Nurul Huda (2013)
System of rice intensification (SRI) is a methodology innovation used in sustainability for social development.It is increasingly recognized worldwide as a suitable model for creating environmental, economic and social sustainability in agriculture for the 21st century.There are many research has proven that sustainable agriculture has many advantages such as cost effectiveness in reducing water consumption, balancing the ecosystem and being environmental friendly.It increases the resistance towards crop diseases and protects the soil and diversity of the organism.In addition, SRI as an organic fanning management provides better quality food which tastes better, is safer and healthier.So, this study was undertaken to understand SRI as sustainable paddy farming practice in two selected areas in West Malaysia.This study employed a qualitative research.Data were collected through field work observation and interviews.The findings of this study show there are several similarities and differences in the practice of paddy farming in Sik and Bandar Baru Tunjong.The finding shows model of sustainable paddy farming practices can be divided in to characteristics of sustainable practices characteristics, sustainable paddy farming practices and the challenges.Implication of this study is able to motivate farmers in sustainable management practices for rice cultivation.